About the necessary and sufficient condition for the existence validation of functional test of minimum possible length for a one-dimensional iterative patterns - Tymoshkin, O. I. (Science and Transport Progress, 2008)
The problem of confidence testing applying to the regular iterative circuits is considered. Total number of such circuits from one class is estimated.